1985
DOI: 10.1113/jphysiol.1985.sp015762
|View full text |Cite
|
Sign up to set email alerts
|

Canine bombesin‐like gastrin releasing peptides stimulate gastrin release and acid secretion in the dog.

Abstract: SUMMARY1. The synthetic mammalian bombesin-like peptides, canine gastrin releasing peptide 27, 23 and 10, and porcine gastrin releasing peptide 27 were compared with amphibian bombesin 14 and 10 during intravenous infusions into six conscious dogs with chronic gastric cannulae.2. Gastrin and gastrin releasing peptide were measured in peripherally sampled venous blood by radioimmunoassay and gastric acid secretions were collected.3. All forms of gastrin releasing peptide stimulated gastrin release and gastric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Therefore, EGF may stimulate gastrin gene expression in addition to its role as a luminal growth factor. Antral G cells are also stimulated by neuropeptides released from antral nerves, such as gastrin-releasing peptide (GRP) (10,11) and vasoactive intestinal peptide (VIP) (4). Although studies ofisolated G cells show that GRP stimulates gastrin secretion (12,13), the effect of GRP on gastrin gene expression has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, EGF may stimulate gastrin gene expression in addition to its role as a luminal growth factor. Antral G cells are also stimulated by neuropeptides released from antral nerves, such as gastrin-releasing peptide (GRP) (10,11) and vasoactive intestinal peptide (VIP) (4). Although studies ofisolated G cells show that GRP stimulates gastrin secretion (12,13), the effect of GRP on gastrin gene expression has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…in enteric nerves that control gastrin secretion, were incubated with the GRP antibody used for neurochemical coding (goat) and a well-characterized antibody that was raised in rabbits (45). Both antibodies stained the same DRG neurons, and both stained neurons of the myenteric plexus and mucosal nerve fibers of the gastric antrum (Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI64551DS1).…”
Section: Tgr5 Is Expressed By Peptidergic Neurons Of the Drgmentioning
confidence: 99%
“…Bunnet et al (29) demonstrated that neuromedin C stimulated gastrin release and gastric acid secretion in conscious dogs with gastric cannulae. This suggested that the mechanism via gastric acid secretion also had a stimulatory effect on the pancreas.…”
Section: Discussionmentioning
confidence: 98%